Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1166/jnn.2015.9186
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Lipid Carriers as a Strategy to Improve the <I>In Vitro</I> Schistosomiasis Activity of Praziquantel

Abstract: Praziquantel (PZQ) is a pyrazinoisoquinoline anthelmintic that was discovered in 1972 by Bayer Germany. Currently, due to its efficacy, PZQ is the drug of choice against all species of Schistosoma. Although widely used, PZQ exhibits low and erratic bioavailability because of its poor water solubility. Nanostructured lipid carriers (NLC), second-generation solid lipid nanoparticles, were developed in the 1990s to improve the bioavailability of poorly water soluble drugs. The aim of this study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 33 publications
(45 reference statements)
2
18
0
Order By: Relevance
“…The schistosomal tegument, as a site of vital and immunological functions for the host response and parasite survival[ 12 ],may present a therapeutic target for drugs having antischistosomal activity. This can be supported by the enhanced tegument damage, induced by PZQ nanometric delivery systems via increasing drug concentration and/or activity [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The schistosomal tegument, as a site of vital and immunological functions for the host response and parasite survival[ 12 ],may present a therapeutic target for drugs having antischistosomal activity. This can be supported by the enhanced tegument damage, induced by PZQ nanometric delivery systems via increasing drug concentration and/or activity [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Different strategies have been proposed for improvement of PZQ delivery in human bodies, including solid dispersion of PZQ in polyvinylpyrrolidone (PVP) [6,9] and other excipients, such as cyclodextrins [10,11] and solid lipid nanoparticles (SLN). [12,13] Encapsulation of PZQ in polymer nanoparticles and microparticles also constitutes a promising alternative for enhancement of PZQ dissolution rates in body fluids and masking of the inherent bitter taste. [2,8,[14][15][16] Particularly, nanotechnologies have helped the development of more efficient drug delivery systems, expanding the range of pharmaceutical formulation products.…”
mentioning
confidence: 99%
“…Several studies revealed an enhanced safety profile for lipid-carrier nanoformulations [23]. Moreover, PZQ showed an enhanced safety profile when incorporated in nanostructured lipid carriers [67], but liposomes and lipid emulsions as drug delivery systems revealed major drawbacks of drug leakage, hydrolysis, possible particle growth and instability during storage [22]. PZQ in nanoclay revealed significantly higher bioavailability and efficacy were recorded; nonetheless, there have been significant changes in haematological analysis and alterations in the cellular electrolyte balance in normal rats following the administration of large doses of montmorillonite clay [6870].…”
Section: Discussionmentioning
confidence: 99%